Biodiversity of Rambut Cave Sale Central Java. Issue 1 (November 2021) - Rachmawati, S; Matin, H H A; Suhardono, S; Setyono, P; Kusumaningrum, L; Rinawati, S; Sholiqin, M
Abstract: Rembang zone karst area stretches from Central Java to Madura Islands. This area is the most significant water or groundwater basin (CAT) area in Rembang Regency, often known as Watuputih Mountains or Karst Area. Watuputih Groundwater Basin is a karst area that is characterized by the formation of several caves. Rambut Cave is one of the caves in Watuputih area located to the east of Watuputih with coordinate's point −6.8783, 111.5534. There are seven types of flora found in the Rambut Cave, namely Horseshoe Bats, Bent-Wing Bats, Ants, Geckos and Crickets, Forest Grasshoppers, and Snails. While the flora was found, there are six types of Bauhinia scandens, Suweg, Mahogany, Drypetes littoralis, Yellow Palm, and Teak trees. The study results obtained the Flora Diversity Index Value H=0.687, which belongs to the low category, and the value of Fauna Diversity Index H'=1.414, which belongs to the medium category.